Research and Technology Buildings : A Design Manual - Braun, Hardo (Design Manuals, 2005)
A handbook on planning and designing architecture for research and technology, with 70 up-to-date international case studies of built works by architects such as Foster and Partners, Nicholas Grimshaw, Herzog & de Meuron, Sauerbruch Hutton, and Nicholas Grimshaw.